(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article discusses reduplication in English and Uzbek languages as a phono-morphological phenomenon. It studies the interpretation of the concept of reduplication, its degree of investigation and classification principles comparatively in English and Uzbek linguistics.